English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1 answers

tanh is defined as:

tanh(x) = (e^x - e^(-x))/(e^x + e^(-x))

Also by the rules of logs,

.5 ln(3) = ln(3^(.5))

Since e^x and ln(x) are inverse functions,

tanh(.5ln(3)) = (3^(.5) - 3^(-.5))/(3^(.5) + 3^(-.5))

Factoring out 3^(-.5) from top and bottom:

(3^(-.5) (3 - 1))/(3^(-.5) (3 + 1))

Simplifying and canceling:

(3 - 1)/(3 + 1) = 2/4 = 1/2

2007-01-07 05:44:17 · answer #1 · answered by Jim Burnell 6 · 0 0

fedest.com, questions and answers